Keck spectroscopy of faint 3 < z < 7 Lyman break galaxies - I. New constraints on cosmic reionization from the luminosity and redshift-dependent fraction of Lyman alpha emission - Stark, D; Ellis, R; Chiu, K; Ouchi, M; Bunker, A (2010)
We present the first results of a new Keck spectroscopic survey of UV faint Lyman break galaxies in the redshift range 3 < z < 7. Combined with earlier Keck and published European Southern Observatory (ESO) VLT data, our spectroscopic sample contains more than 600 dropouts offering new insight into the nature of sub-L* sources typical of those likely to dominate the cosmic reionization process. In this first paper, in a series discussing these observations, we characterize the fraction of strong Lyα emitters within the continuum-selected dropout population. By quantifying how the 'Lyα fraction', xLyα, varies with redshift, we seek to constrain changes in Lyα transmission associated with reionization. In order to distinguish the effects of reionization from other factors which affect the Lyα fraction [e.g. dust, interstellar medium (ISM) kinematics], we study the luminosity and redshift-dependence of the Lyα fraction over 3 ≲z≲ 6, when the intergalactic medium (IGM) is known to be ionized. These results reveal that low-luminosity galaxies show strong Lyα emission much more frequently (xLyα= 0.47 ± 0.16 at MUV=-19) than luminous systems (xLyα= 0.08 ± 0.02 at MUV=-21), and that at fixed luminosity, the prevalence of strong Lyman α emission increases moderately with redshift over 3 < z < 6 (d xLyα/d z= 0.05 ± 0.03). Based on the bluer mean UV slopes of the strong Lyα emitting galaxies in our data set (〈Β〉Lyα-〈Β〉noLyα=-0.33 ± 0.09 at MUV=-20.5) we argue that the Lyα fraction trends are governed by redshift and luminosity-dependent variations in the dust obscuration, with likely additional contributions from trends in the kinematics and covering fraction of neutral hydrogen. Using the limited infrared spectroscopy of candidate zreversed tilde 7 galaxies, we find a tentative decrease in the Lyα fraction by a factor of >1.9 with respect to the predicted zreversed tilde 7 value, a result which, if confirmed with future surveys, would suggest an increase in the neutral fraction by this epoch. Given the abundant supply of z and Y drops now available from deep Hubble WFC3/IR surveys, we show it will soon be possible to significantly improve estimates of the Lyα fraction using optical and near-infrared multi-object spectrographs, thereby extending the study conducted in this paper to 7 ≲z≲ 8. © 2010 The Authors. Journal compilation © 2010 RAS.